The Characteristic Trends in Latvian Regional Press: Changes in the Traditional Functions of the Press, the Aspects of Identity and Cultural Diversity - Liepa, Ditė; Liepa, Zenta (Acta humanitarica academiae Saulensis, 2025)
Latvian regional press has been a staple of the state media environment for decades despite the fact that its readership is shrinking with each year due to objective reasons: young people move away in search for a better life in accordance with their education and professional capabilities, the already aging population is growing older; moreover, in rural Latvia, most residents have a lower income and purchasing power in comparison to the urban population, especially Rigans. However, in spite of these factors, many Latvians still try to save money especially for “their local paper”, thus ensuring the viability of regional press that has been enjoying the readers’ support for decades as a traditional value. In these pages readers find advice on how to take care of both their own and their animals’ health, how to grow in their garden something that the neighbour does not have, how to economise and save enough from one’s small income to visit Lithuania and Estonia, and, if one wants to dream of far-off lands, it is made possible at a tourism evening, when a traveller’s tale and videos transport the audience to Guatemala. Moreover, when reporting on regional news, local dialectal words are used, reminding the readers both not to forget and use them. Regional press teaches to accept life as it is. In it the readers can learn how to make an annual visit to a sanatorium and prepare meals for 2 euros a day – and not to complain about it; they are advised not to wait for miracles and find joy in the little things, as true strength can be found within, and one can learn to manage, not to complain, and set an example to the neighbours.Heads of regional newspapers admit that nowadays regional press has attained a special status: it informs its audience on everything of importance in the rural areas of Latvia, thus acting as a modern source of cultural environment, language and community togetherness. Moreover, being acutely aware of the limited cultural event and socialisation options, the newspapers also fulfil social, welfare, and healthcare functions; thus, the postman often becomes the most welcome weekly guest in the lonely homes that are cut off from the problems of urban life. Many people have left the rural areas and gone into economic exile; therefore, nearly every newspaper prints a story both on those locals who have found happiness and success elsewhere and those who have come back to Latvia and try to use their experience to strengthen their region and Latvia as a whole. These different personal stories make it possible to examine the identity of the new generation and its sense of belonging to Latvia and the Latvian language.
Keywords: regional press; thematic diversity; changes in functions; family roots; state; language; national identity of the new generation